2021
DOI: 10.1002/ejic.202100785
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosulfonylferrocene, (Trifluoromethylsulfonyl)ferrocene and New Ferrocenyl Sulfonates: Directed ortho Lithiation and New Anionic Thia‐Fries Rearrangements at Ferrocene

Abstract: Dedicated to the 70th anniversary of the discovery of ferroceneFerrocenyl triflates are known to undergo anionic thia-Fries rearrangements at low temperature in high yields. In order to expand the scope of this reaction, ferrocenyl sulfonates and sulfonylferrocenes were prepared and their reactivity investigated. Treatment of ferrocenyl fluorosulfonate with lithium 2,2,6,6-tetramethylpiperidide gave rise to a new anionic thia-Fries rearrangement at ferrocene. The formation of a rare oxathiine was observed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…So far, (aryl triflate)tricarbonylchromium and ferrocenyl triflates were the only organometallic complexes, at which it had been observed. [22][23][24][25]32,33] The first step of the anionic thia-Fries rearrangement is the deprotonation at the ortho position next to the triflate substituent. In view of the positive charge of the cobaltocenium ion anticipating an increased CÀ H acidity we saw the chance to realize the rearrangement with a weaker base than LDA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, (aryl triflate)tricarbonylchromium and ferrocenyl triflates were the only organometallic complexes, at which it had been observed. [22][23][24][25]32,33] The first step of the anionic thia-Fries rearrangement is the deprotonation at the ortho position next to the triflate substituent. In view of the positive charge of the cobaltocenium ion anticipating an increased CÀ H acidity we saw the chance to realize the rearrangement with a weaker base than LDA.…”
Section: Resultsmentioning
confidence: 99%
“…[48] In the course of our investigations with ferrocene systems it was shown that the anionic thia-Fries rearrangement does not take place with ferrocenyl mesylate or tosylate. [23] This gave rise to check, if the corresponding cobaltocenium salts behave accordingly, or if the rearrangement took place with them. When cyclopentadienone complex 6 was treated with methanesulfonic anhydride, the required reaction temperature was higher than with triflic anhydride, presumably due to the decreased electrophilicity of the anhydride.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…1, top right). 46 Further functionalization was demonstrated by a deprotolithiation-electrophilic trapping sequence using lithium 2,2,6,6-tetramethylpiperidide (LiTMP) as the base and Fig. 1 Ferrocenesulfonyl fluorides already reported.…”
Section: Introductionmentioning
confidence: 99%